Bacteriophages of Clostridium perfringens - Seal, Bruce S.; Volozhantsev, Nikolay V.; Oakley, Brian B.; Morales, Cesar A.; Garrish, Johnna K.; Simmons, Mustafa; Svetoch, Edward A.; Siragusa, Gregory R. (IntechOpen, 2012)
None